The Dilemma of Geographical Enlargement from the Perspective of a Central Eastern European Country: Croatia - Vasiljević, Snježana (Maastricht 30: A Central European Perspective, 2025)
The link between diverse European national cultures and the bridge between old and new Member States can be seen in the concept of European integration. However, what are considered fundamental values in the European Union (EU), in the rest of Europe that is outside the EU, they are not perceived in the same way. Furthermore, candidate countries have chosen to resist these values precisely by emphasising traditions, legal culture and fundamental constitutional values which differ significantly from those of the EU because of their long wait in the European Union’s lobby. The EU’s conditionality policy initially crafted for Central and Eastern European countries (CEE) interested in joining the EU expanded to include the Western Balkan region. The lack of a monitoring mechanism after accession has led to very slow and limited progress in fundamental rights’ protection and the adoption of the fundamental values set out in the Maastricht Treaty, although the implementation of international and European standards rights in Croatian legislation was the result of the pre-accession conditionality proposed by the Copenhagen Summit. Keywords: geographical enlargement, conditionality policy, fundamental values, fundamental rights, rule of law